Evaluasi Program GEMERLAP di Desa Candisari Kecamatan Sambeng: Studi Deskriptif pada Kelompok Tani Holtikultura “Godong Ijo Sejahtera” ( Evaluation of GEMERLAP Program in Candisari Village, Sambeng Subdistrict: Descriptive Study of Horticultural Farmers ' - Milla, Anikdatul; Murdiyastuti, Anastasia; A, Anwar (e-Sospol, 2019)
AbstractThis research aims to evaluate the program of the Movement to Build a Village Based Society Economy inCandisari village, Sambengsub district. This descriptive research employed a qualitative approach. Theinformants were determined purposively. Research data were collected through observation, interview, anddocumentation. Data were analyzed by using interactive analysis of Miles and Huberman which consistedof data reduction, data presentatio n, and drawing conclusion. To test data validity, researchers used sourcetriangulation. The theory used in evaluating the Movement to Build a Village Based Society Economy wasWilliam N Dunn's evaluation theory. Based on the findings, from the six William N Dunn criteria used toevaluate, only two were fulfilled namely leveling and accuracy. While the other four criteria, namelyeffectiveness, efficiency, adequacy, and responsiveness were still poor. This condition was due to severalfactors, namely the la ck of optimal effort of government in implementing the program and overcoming theepidemics. This condition happened because the Calina Papaya program was not included in the RoadMap of the Office of Food Crops, Plantation, and Horticulture.Keywords:pro gram evaluation , GEMERLAP